1986
DOI: 10.1063/1.1138693
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectrometer for a single electrodynamically levitated microparticle

Abstract: A spectrometer for measuring the fluorescence emission from a single trapped aerosol particle is described. This device consists of a particle generator, an electrodynamic levitator, an excitation source, and detection optics and electronics. Provision is made to cool the sample chamber, and spectra can be obtained in real time. Typical spectra from particles containing organic laser dyes are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(47 citation statements)
references
References 14 publications
1
46
0
Order By: Relevance
“…Particles studied in this work were 20-to 30-/•m-diameter sulfuric acid droplets suspended in the quadrupole trap. The droplets are injected using a microparticle on-demand picopipette [Arnold and Folan, 1986]. As the particle is cooled down, a slow flow of nitrogen (100 cm 3 m -• STP) is passed through the quadrupole trap chamber.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Particles studied in this work were 20-to 30-/•m-diameter sulfuric acid droplets suspended in the quadrupole trap. The droplets are injected using a microparticle on-demand picopipette [Arnold and Folan, 1986]. As the particle is cooled down, a slow flow of nitrogen (100 cm 3 m -• STP) is passed through the quadrupole trap chamber.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The trap enables a charged particle (glycerol droplet) to be held stationary by a combination of ac and dc fields. While the dc field offsets the gravitational force, the ac field works with the trap's geometry to create a quasi-stable area in the central region [11][12][13]. The glycerol droplets are created by a grounded atomizer, and these droplets are passed through a conducting ring held at high voltage (∼800 V).…”
Section: Methodsmentioning
confidence: 99%
“…EPTs have been used to perform Raman spectroscopy (Fung and Tang, 1989), Fourier transform infrared spectroscopy (Grader and Arnold, 1987), and fluorescence analysis from single suspended aerosols (Arnold and Folan, 1986). The extreme sensitivity of fluorescence measurements was demonstrated by Whitten et al (1991) who demonstrated single molecule detection in suspended particles.…”
Section: Experimental Single Particle Balance Backgroundmentioning
confidence: 99%